Pemilihan Sistem Air Limbah-Lumpur Tinja Komunal Menggunakan Analisis Klaster Hirarki - Elis Hastuti; Benny Joy; Unang Supratman (Jurnal Permukiman, 2024)
Management of fecal sludge from decentralized wastewater treatment plants (WWTP) is a challenge in settlements have limited access to centralized sludge treatment facilities. This paper reviewed the  selection and development strategy of integrated communal WWTP and fecal sludge treatment (SIPAL-LT).  The dominant factors influence sustainability of SIPAL-LT are treatment system, management, environment, and community characteristic. The development of  SIPAL-LT were determined  based on the sustainability profile of location study, technology selection, and development profile of SIPAL-LT. The selection and priority  of SIPAL-LT system were analyzed by hierarchical cluster, while  development strategies by quadrants method. The SIPAL-LT that feasible to develop is in a cluster that has characteristic, including domestic wastewater treated categorized low-medium pollution, existing user of communal WWTP more than 60% of capacity, fecal sludge  categorized light pollution, maintenance index categorized low- medium, overall effectiveness equipment  index of communal WWTP more than 60%, and participation stage categorized medium-high.  The best SIPAL-LT in study location has communal WWTP applied biofilter or digester anaerobic technology, while planning of fecal sludge treatment applied constructed wetland or sludge dyring bed combined by co-composting.